Perkaitan antara faktor-faktor terpilih dalam pengurusan kualiti menyeluruh (TQM) dengan pengurusan keselamtan menyeluruh (TSM) : satu kajian di syarikat MLNG, Bintulu - Shelly, Anak Unsa. (Universiti Malaysia Sarawak (UNIMAS), 2005)
The purpose ofthis study was to highlight the correlation between selected factors in Total Quality A1anagement (IQM) with Total Softty Management (TSM). The independents variables for this study were empowerment, teamwork. safety training and development. continual process improvement and long-term commitment. While. the dependent variable was Total Safety Management (TSM). 49 respondents were selected as a sample. A questionnaire was used for collecting data. This collected data has are analyse by using the Statistical Package ofSocial Science (SPSS) . From the Pearson Correlation analyses. the studies showed there was are significant relationship between teamwork. safety training and development. and continual process improvement wilh TSM. The finding of the Regression Linear analyses revealed that the dominant factor for this study was continual process improvement. From this study, continual process improvement indicated as a dominant factor and it must be emphasize in helping the TSM in organization.